RD Sharma class 10 solutions Chapter 8 Quadratic Equations Ex 8.3

RD Sharma class 10 solutions Chapter 8 Quadratic Equations Ex 8.3

RD Sharma Class 10 Solutions Quadratic Equations Exercise 8.3

Solve the following quadratic equations by factorization.
Question 1.
(x – 4) (x + 2) = 0
Solution:
(x – 4) (x + 2) = 0
Either x – 4 = 0, then x = 4
or x + 2, = 0, then x = -2
Roots are x = 4, -2

Question 2.
(2x + 3) (3x – 7) = 0
Solution:

Question 3.
3x2 – 14x – 5 = 0 (C.B.S.E. 1999C)
Solution:

Roots are x = 5, $\frac { -1 }{ 3 }$

Question 4.
9x2 – 3x – 2 = 0
Solution:

Question 5.

Solution:

Question 6.
6x2 + 11x + 3 = 0
Solution:

Question 7.
5x2 – 3x – 2 = 0
Solution:

Question 8.
48x2 – 13x – 1 =0
Solution:

Roots are x = $\frac { 1 }{ 3 }$, $\frac { -1 }{ 16 }$

Question 9.
3x2 = – 11x – 10
Solution:

Question 10.
25x (x + 1) = -4
Solution:

Question 11.
16x – $\frac { 10 }{ x }$= 27 [CBSE 2014]
Solution:

Question 12.

Solution:

Question 13.
x – $\frac { 1 }{ x }$= 3, x ≠ 0 [NCERT, CBSE 2010]
Solution:

Question 14.

Solution:

Question 15.

Solution:

Question 16.
a2x2 – 3abx + 2b2 = 0
Solution:

Question 17.
9x2 – 6b2x – (a4 – b4) = 0 [CBSE 2015]
Solution:

Question 18.
4x2 + 4bx – (a2 – b2) = 0
Solution:

Question 19.
ax2 + (4a2 – 3b)x- 12ab = 0
Solution:

Question 20.
2x2 + ax – a2 = 0
Solution:

Question 21.

Solution:

x2 = 16
x = ±4

Question 22.

Solution:

Question 23.

Solution:

Question 24.

Solution:

Roots are 4, $\frac { -2 }{ 9 }$

Question 25.

Solution:

Question 26.

Solution:

Question 27.

Solution:

Question 28.

Solution:

Question 29.

Solution:

Question 30.

Solution:

Question 31.

Solution:

Question 32.

Solution:

Question 33.

Solution:

Question 34.

Solution:

Question 35.

Solution:

Question 36.

Solution:

Question 37.

Solution:

Question 38.

Solution:

Question 39.

Solution:

Question 40.

Solution:

Question 41.
x² – (√2 + 1) x + √2 = 0
Solution:

Question 42.
3x² – 2√6x + 2 = 0 [NCERT, CBSE 2010]
Solution:

Question 43.
√2 x² + 7x + 5√2 = 0
Solution:

Question 44.
$\frac { m }{ n }$x² + $\frac { n }{ m }$= 1 – 2x
Solution:

Question 45.

Solution:

Question 46.

Solution:

Question 47.

Solution:

Question 48.

Solution:

Question 49.

Solution:

Question 50.
x² + 2ab = (2a + b) x
Solution:

Question 51.
(a + b)2 x² – 4abx – (a – b)2 = 0
Solution:

Question 52.
a (x² + 1) – x (a² + 1) = 0
Solution:

Question 53.
x² – x – a (a + 1) = 0
Solution:

Question 54.
x² + (a + $\frac { 1 }{ a }$) x + 1 = 0
Solution:

Question 55.
abx² + (b² – ac) x – bc = 0 (C.B.S.E. 2005)
Solution:

Question 56.
a²b²x² + b²x – a²x – 1 = 0 (C.B.S.E. 2005)
Solution:

Question 57.

Solution:

Question 58.

Solution:

Question 59.

Solution:

⇒ x = 0
x = 0, -7

Question 60.

Solution:

Question 61.

Solution:

Question 62.

Solution:

Solution 30:

+